Kepastian Hukum Penyelesaian Sengketa Atas Kepemilikan Ganda Terkait Dengan Pembebasan Tanah Untuk Kepentingan Umum - Ade Slamet Riadi; Irawan Soerdjo; Ahmad Yani (JOURNAL of LEGAL RESEARCH, 2022)
The land issue is a problem that is most closely related to the basic rights of the community. Land acquisition for the use of public interest is related to land that has a social function. Along with the high value and benefits of land, many people try to obtain proof of land ownership by having fake certificates, where the data on the certificate does not match what is in the land book. This study uses a normative juridical method which is supported by empirical juridical. Based on the results of research on court decisions Number 482/Pdt/2018/Pt.Bdg. shows that legal certainty over the dual ownership certificate has been achieved with the judge's decision granting the Plaintiff/Plaintiff's claim as the owner of the original land rights. Therefore, the National Land Agency must be more careful in making physical data and juridical data in carrying out the land registration process, and also for the next case the judge is more careful in examining the chronology of the occurrence of ownership of land rights, because it involves the certainty of the subject and object of ownership of rights. over the ground.